Study on the thermal conductivity of rabbit pelts - Yuqing M.; Shihong L. (Rabbit production in hot climates, 1994)
The thermal conductivity of different parts of twenty-one local meat-rabbit pelts were measured. The results show that there are extremely significant correlations between the pelt thickness and the cooling time (T), cool coefficient (h) and cooling value (H). Their correlation coefficients (r) are 0.94, -0.99 and -0.99 respectively. the differences among different pelt parts are extremely significant (p less than 0.01), too.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)